UPAYA PEMBINAAN ANAK DIDIK OLEH LEMBAGA PEMBINAAN KHUSUS ANAK PERSPEKTIF MAQĀṢID AL-SYARĪ’AH (STUDI DI LPKA KELAS II TENGGARONG) - Wati, Widya; Iswanto, Bambang; Syakur, Abdul (Fasya UIN Sultan Aji Muhammad Idris Samarinda, 2025)
Abstract: One of the factors, such as the lack of attention and parental involvement in educating, nurturing, and providing the rights of children, can result in the child committing criminal acts and eventually coming into contact with the law. Therefore, during their sentence, the Juvenile Correctional Institution, hereinafter referred to as the institution, plays a role in providing guidance to children who are in conflict with the law. This research is a qualitative study with a normative-empirical legal method, descriptive in nature, using a statutory approach. The data sources come from primary and secondary data. The data collection techniques used include observation, interviews, and documentation, with three procedures for data analysis: data reduction, data presentation, and drawing conclusions. Based on the research findings, the efforts made by the Juvenile Correctional Institution Class II Tenggarong consist of religious guidance, education, skills/interests & talents, each manifested in several activities, providing the children's rights, fulfilling their needs, and offering healthcare services that encompass both physical and mental health. Secondly, from the perspective of Maqāṣid Al-Syarī’ah, there are three points of guidance by the Juvenile Correctional Institution Class II Tenggarong that are categorized as Dharuriyyat (essential needs), namely religious activities under the category of Hifdz al-din (preservation of religion), such as mandatory and voluntary communal prayers, BTQ (Qur'an reading), study of religious gatherings, and the Bible study. Then, healthcare services under the category of Hifdz nafs (preservation of life), which include providing nutritious food, rest periods, health check-ups, exercise, and counseling with psychologists. Lastly, education under the category of Hifdz aql’ (preservation of intellect), which includes formal education, package programs, and religious classes. Furthermore, activities related to skill development, interests, and talents fall under the category of Hajiyyat (complementary needs). Abstrak: Salah satu faktor seperti kurangnya perhatian dan peran orang tua dalam hal mendidik, mengasuh, dan pemberian hak-hak anak dapat mengakibatkan anak melakukan tindak pidana dan akhirnya berurusan dengan hukum. Sehingga selama menjalani masa pidananya, Lembaga Pembinaan Khusus Anak yang selanjutnya memiliki peran dalam memberikan pembinaan terhadap anak yang berkonflik dengan hukum tersebut. Jenis penelitian ini adalah penelitian kualitatif dengan metode hukum normatif-empiris yang bersifat deskriptif dengan menggunakan pendekatan perundang-undangan (Statue Approach). Sumber data berasal dari data primer & sekunder. Teknik pengumpulan data yang digunakan yaitu observasi, wawancara, dan dokumentasi, serta menggunakan tiga prosedur dalam menganalisis data, yaitu reduksi data, penyajian data, dan penarikan kesimpulan. Berdasarkan hasil penelitian, upaya yang diberikan oleh Lembaga Pembinaan Khusus Anak Kelas II Tenggarong yaitu terdiri dari pembinaan keagamaan, pendidikan, keterampilan/minat & bakat yang masing-masing pembinaan diwujudkan dalam beberapa kegiatan, pemberian hak-hak anak binaan, pemenuhan kebutuhan yang dibutuhkan, serta layanan kesehatan yang melingkupi kesehatan fisik maupun kesehatan mental. Yang kedua, dalam perspektif Maqāṣid Al-Syarī’ah, terdapat tiga poin pembinaan oleh Lembaga Pembinaan Khusus Anak Kelas II Tenggarong yang bersifat Dharuriyyat, yaitu kegiatan keagamaan sebagai kategori Hifdz al-din yaitu shalat fardhu dan sunnah berjamaah, BTQ, kajian majlis ta’lim dan kajian alkitab. Kemudian layanan kesehatan sebagai kategori Hifdz nafs yang meliputi pemberian makanan yang bergizi, pemberian waktu istirahat, periksa kesehatan, olahraga konseling dengan psikolog. Kemudian pendidikan sebagai kategori Hifdz aql’, meliputi pendidikan formal, kejar paket, dan kelas keagamaan. Selanjutnya ialah yang bersifat Hajiyyat mencakup kegiatan pengembangan keterampilan, minat dan bakat.